PNPLA3-Associated Steatohepatitis: Toward a Gene-Based Classification of Fatty Liver Disease - Krawczyk, Marcin; Portincasa, Piero; Lammert, Frank (Seminars in Liver Disease, 2013)
Nonalcoholic fatty liver disease is one of the most common hepatic disorders worldwide. Given the high-calorie nutrition of children and adults, nonalcoholic fatty liver disease (NAFLD) is expected to become a major cause of cirrhosis and eventually liver transplantation. Familial clustering and ethnic differences indicate that genetic factors contribute to NAFLD. Recently, the common variant p.I148M of the enzyme adiponutrin (PNPLA3) has emerged as a major genetic determinant of hepatic steatosis and nonalcoholic steatohepatitis as well as its pathobiological sequelae fibrosis, cirrhosis, and hepatocellular cancer. PNPLA3 encodes a lipid droplet-associated, carbohydrate-regulated lipogenic and/or lipolytic enzyme. Homozygous carriers of the PNPLA3 variant are prone to develop cirrhosis in the absence of other risk factors such as alcohol or viral hepatitis. Here we review the plethora of studies that unraveled the association between PNPLA3 and NAFLD in children and adults, discuss its distinct effects on liver and metabolic traits, and introduce the term PNPLA3-associated steatohepatitis (PASH) as a novel gene-based liver disease. Given the prevalence of the risk allele in 40 to 50% of Europeans, the authors conclude that PNPLA3 should be considered in the diagnostic workup of fatty liver disease and that homozygous risk allele carriers might benefit from careful cancer surveillance.
Keywords: adiponutrin; genomics; genetic susceptibility; nonalcoholic steatohepatitis; steatosis